The Effect of Leadership Style and Organizational Culture in Determining the Employee Performance of Koperasi Syariah During Pandemic Covid-19 at South Cimahi Region - Hasanuddin, Maulana; Hermina, Nurul (Universitas Proklamasi 45, 2024)
Successful organizations have main characteristics that differentiate them from failed organizations, namely leadership that is dynamic and effective, strong in vision and firm in attitudes and principles, able to anticipate the future of the organization and take opportunities from existing changes so that it can direct the organization to achieve the goal. deliberately. The purpose of this research is to test and analyze the influence of Leadership Style and Organizational Culture on the Employee Performance of Sharia Cooperative (Koperasi Syariah) in South Cimahi Region, both simultaneously and partially. This research is quantitative. The research method used was descriptive and verification to analyze employees of the South Cimahi Region Sharia Cooperative, with a sample of 50 employees. Based on the results of research and discussion, it was found that Leadership Style shows a strong relationship influence on employee performance compared to organizational culture in the medium category. This shows that the better the leadership style, the better the employee's performance. Organizational culture and employee performance will follow. It can be concluded that the transformational leadership style can change the South Cimahi Regional Sharia Cooperative to the concept of struggle. The transformation of the South Cimahi Regional Sharia Cooperative was born from the breakthrough of its leaders who were firm, innovative, and brave.